2005
DOI: 10.1107/s1600536805014844
|View full text |Cite
|
Sign up to set email alerts
|

2-(2,4-Dihydroxybenzoyl)benzoic acid

Abstract: In the title structure, C14H10O5, the angle between the planes formed by the 2,4‐di­hydroxy­benzoyl and o‐benzoic acid moieties is 87.12 (4)°. In addition to an intramolecular O—H⋯O hydrogen bond, intermolecular O—H⋯O hydrogen bonds (H⋯O = 1.76 and 1.89 Å) connect mol­ecules to form a two‐dimensional network parallel to (10).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…For related literature, see: Fronczek et al (1987); Kokila et al (1992); Liebich (1979); Li et al (2005); van Rooyen & Breytenbach (1988).…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…For related literature, see: Fronczek et al (1987); Kokila et al (1992); Liebich (1979); Li et al (2005); van Rooyen & Breytenbach (1988).…”
Section: Related Literaturementioning
confidence: 99%
“…The title compound is currently being used as a starting material for synthesis of new chelating ligands. There have been several derivatives of resorcinol published in the literature (Fronczek et al, 1987;Kokila et al, 1992;Liebich, 1979;Li et al, 2005;van Rooyen & Breytenbach, 1988). The compound most similiar to (I) (Kokila et al, 1992) has two acetyl groups found in the 4 and 6 positions.…”
Section: S1 Commentmentioning
confidence: 99%